The Effect of Recycled Glass Powder and Reject Fly Ash on the Mechanical Properties of Fibre-Reinforced Ultrahigh Performance Concrete - Shi Cong Kou; Feng Xing (Advances in Materials Science and Engineering)
This paper presents an experimental study for the purpose of reducing the cost of producing ultrahigh performance fibre-reinforced concrete (UHPFRC). Reject fly ash (r-FA) and recycled glass powder (GP) were examined as replacement materials for the silica sand and cement used to prepare UHPFRC, respectively. In addition, curing UHPFRC specimens at 25∘C and 90∘C was investigated to determine differences in mechanical properties. The results showed that using r-FA and GP reduces the flowability of fresh UHPFRC. The use of GP increased the mechanical properties of the UHPFRC. Moreover, the test results indicate a significant improvement in the mechanical properties of plain concrete by the inclusion of r-FA as partial replacement of fine aggregate (sand) and can be effectively used in UHPFRC. Furthermore, specimens cured at 25∘C give lower compressive strength, flexural strength, and fracture energy than specimens cured at 90∘C.